Gas permeation properties of nickel nanoparticle-embedded PPO/PVP polymers based carbon membrane. (2022) - Harinkhere, Disha; Kaurav, Netram
Abstract: Mixed-matrix membranes (MMM) of thermally stable poly (2, 6-dimethyl-1, 4-phenyleneoxide) (PPO) polymer and thermally labile Polyvinylpyrrolidone (PVP) polymer, PPO/PVP, and its nickel nanoparticle (NP)-incorporated, PPO/PVP/Ni, were prepared to study their gas separation properties. Field emission scanning electron microscopy (FESEM) images were used to study their surface morphology, surface porosity, average pore size, and X-ray diffraction (XRD) patterns for crystallite size of Ni NPs and their phase purity. In particular, surface study of MMMs revealed that due to the inclusion of nickel NPs, the pore structure of the PPO/PVP/Ni membrane has been decreased. The gas permeation of H2, O2 and N2 was measured by single gas permeation method. The PPO/PVP/Ni exhibits much higher permeation results as compared to that of PPO/PVP. Additionally, the former provides higher selectivity for the H2 /N2 gas pair as compared to O2 /N2 gas pair. Furthermore, the permeation results show that the incorporating of nickel NPs (1 wt%) to the PPO/PVP/Ni membrane caused the permeances to increase by nearly 45 times when compared to the PPO/PVP membrane.